Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests. (21st February 2014) - Brzostek, Edward R.; Dragoni, Danilo; Schmid, Hans Peter; Rahman, Abdullah F.; Sims, Daniel; Wayson, Craig A.; Johnson, Daniel J.; Phillips, Richard P.
Abstract: Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO2, and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n  = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest (MMSF) in Indiana, and a regional 11‐year record of tree growth ( n  > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA. We show that despite ~26 more days of C assimilation by trees at the MMSF, increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding 'mesophytic' tree species. Given the current replacement of water‐stress adapted 'xerophytic' tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.